Диэлектрическая релаксация Коул-Коула - Novikov, V. V.; Komkova, О. А. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
A model of the microstructure of disordered media exhibiting non-exponential relaxation has been constructed. The proposed model is based on a fractal approach to the structuring of the medium and the identification of hierarchical levels of short-range cluster orders and their components—subclusters. A fractional differential operator was used to derive the Cole-Cole complex susceptibility.